Chronic Urocortin 2 Administration Improves Cardiac Function and Ameliorates Cardiac Remodeling After Experimental Myocardial Infarction. Issue 3 (March 2015) - Ellmers, Leigh J.; Scott, Nicola J. A.; Cameron, Vicky A.; Richards, A. Mark; Rademaker, Miriam T.
Abstract : Abstract: The impact of chronic urocortin 2 (Ucn2) treatment after myocardial infarction (MI) has not previously been investigated. In this study, we examined the effects of 30-day Ucn2 administration (415 μg·kg −1 ·d −1 SC per day) in mice post-MI. Compared with surgical sham + vehicle controls (n = 10), MI + vehicle animals (n = 10) after 30 days demonstrated decreased ejection fraction (75.6 ± 1.2 vs. 43.6% ± 0.8%, P < 0.001) and fractional shortening (38.20 ± 0.83 vs. 18.4% ± 0.54%, P < 0.001) in association with increased heart weight-to-body weight ratio (4.57 ± 0.25 vs. 5.29 ± 0.18, P < 0.01), left ventricular (LV) mass (91 ± 7 vs. 126 ± 8 mg, P < 0.01), LV internal diameters at both systole (1.91 ± 0.14 vs. 3.45 ± 0.09 mm, P < 0.001) and diastole (3.14 ± 0.15 vs. 4.25 ± 0.10 mm, P < 0.001), LV end systolic volumes (0.02 ± 0.01 vs. 0.11 ± 0.01 mL, P < 0.001), and ventricular collagen 1 and β-myosin heavy chain gene expression. Compared with MI + vehicle mice, MI + Ucn2 animals (n = 10) exhibited significantly reduced infarct size (4.00 ± 0.39 vs. 1.83 ± 0.44 mm 2, P < 0.01), heart weight-to-body weight ratio (4.75 ± 0.19, P = 0.06), LV mass (101 ± 6 mg, P < 0.01), LV internal diameters (systole 2.61 ± 0.09 mm, P < 0.001; diastole 3.78 ± 0.09 mm, P < 0.001), and end systolic volumes (0.14 ± 0.02 mL, P < 0.01) in conjunction with improved ejection fraction (65.2% ± 0.9%, P < 0.001) and fractional shortening (18.4 ± 0.5 vs. 30.5% ± 0.5%, P < 0.001). Ucn2 treatment also decreased collagen 1 and β-myosin heavy chain expression. In conclusion, chronic Ucn2 treatment significantly improves cardiovascular function and attenuates cardiac injury and remodeling in experimental MI.